The Global Ruling of Local Crisis Intervention: An Institutional Ethnography of Anti-Violence Work in Kyrgyzstan - Kim, Elena (Violence against women, 2022)
This article analyzes contradictory practices carried out in Kyrgyzstani crisis centers for victims of gender violence resulting in women-clients failing to obtain the protection they seek. These problematic dynamics are shaped by a global apparatus on women’s human rights protection and international standards of practice. Crisis center professionals perform the final activation of this ruling apparatus through textual work driven not by the women’s needs but by the goal of bringing local actions into accord with the “legal framework” organized and expressed by the national anti-violence law and the government’s need to report on it to international treaty bodies.